The Mitochondrial Deubiquitinase USP30 Regulates AKT/mTOR Signaling - Zhang, Ruohan; Ozgen, Serra; Luo, Hongke; Krigman, Judith; Zhao, Yutong; Xin, Gang; Sun, Nuo (Frontiers in Pharmacology, 2022)
Mitophagy is an intracellular mechanism to maintain mitochondrial health by removing dysfunctional mitochondria. The E3 ligase Parkin ubiquitinates the membrane proteins on targeted mitochondria to initiate mitophagy, and USP30 antagonizes this Parkin-dependent mitophagy. AKT/mTOR signaling is a master regulator of cell proliferation, differentiation, survival, and growth. Although mounting evidence showed mitophagy and AKT/mTOR signaling interact with each other during mitophagy, the specific mechanisms between Parkin/USP30 and AKT/mTOR signaling have not been elucidated. This research artificially expressed Parkin and USP30 in Hela cells and compared AKT/mTOR and apoptosis signals between Hela cells, HeLa Parkin cells, and Hela Parkin USP30 cells during mitophagy. The study’s results suggest that Parkin promotes AKT degradation via ubiquitination, which induces cell apoptosis during mitochondrial stress. On the contrary, USP30 protects AKT via deubiquitination. These findings provide new insights into Parkin and USP30’s role in cell apoptosis and physiological and pathological functions of USP30 beyond mitophagy.